The Use of the Card Sort Method in Overcoming Slow Learners in Arabic Subjects at MI Nurul Amal in MI Nurul Amal Bekasi - Syifa Fauziah; Achmad Junaedi Sitika; Nurhasan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Elementary school students generally enjoy fun activities, such as playing. Therefore, teachers must be able to design learning that facilitates students' freedom of movement while remaining engaged in the educational environment or situation. Students also greatly enjoy learning activities conducted in groups and through live demonstrations. By understanding these student characteristics, teachers are expected to be able to create a learning environment that improves the quality and effectiveness of learning. This is tailored to the needs and abilities of elementary school students. (Safitri, 2022)The use of visual-based cards in the card sort method facilitates understanding, strengthens memory, and fosters interest and motivation in learning activities. The card sort learning strategy, combined with game techniques, is expected to help students understand the lesson and understand the classification of the material.The card sort method is a learning method using index cards. This learning technique combines active individual learning techniques with collaborative or cooperative learning techniques.Judging from the results achieved in using this card sort method, there is an influence caused by an event or action on students in carrying out ongoing learning activities, it can be seen that there is a development in students' learning abilities from the way they start to dare to come forward and answer the vocabulary written or explained by the teacher, are more active in answering every question written or explained by the teacher, start to get used to and think that Arabic lessons are fun lessons, start to understand and memorize every vocabulary that has been studied previously.